2012
DOI: 10.1002/mrm.24316
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the radiofrequency heating of metallic devices using a dual‐drive birdcage coil

Abstract: In this work, it is demonstrated that a dual-drive birdcage coil can be used to reduce the radiofrequency heating of metallic devices during magnetic resonance imaging. By controlling the excitation currents of the two channels of a birdcage coil, the radiofrequency current that is induced near the lead tip could be set to zero. To monitor the current, the image artifacts near the lead tips were measured. The electric field distribution was controlled using a dual-drive birdcage coil. With this method, the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 12 publications
4
67
0
Order By: Relevance
“…There is an advantage of less heating using short cables at 4T magnetic fields [117] and showed agreement with water-gel phantom experiments. The summaries of the safety researches of EEG and implants in MRI using animal samples are included in Table 1.…”
Section: Survey Of the Experimental Literature On The Safety Of Scalpsupporting
confidence: 62%
See 1 more Smart Citation
“…There is an advantage of less heating using short cables at 4T magnetic fields [117] and showed agreement with water-gel phantom experiments. The summaries of the safety researches of EEG and implants in MRI using animal samples are included in Table 1.…”
Section: Survey Of the Experimental Literature On The Safety Of Scalpsupporting
confidence: 62%
“…Overall at 0.35T [103] and 1.5T it has been found that risks can be managed under specific configurations (low SAR sequences and often a head transmit-receive coil) and the production of heating is less when DBS equipment are fully implanted [34,59,[104][105][106][107][108][109][110][111][112][113]. In 3T MRI fields and higher [34,59,107,[109][110][111][114][115][116][117][118], similar results in terms of heating have been obtained but more caution is required when dealing with DBS implants and wires as well as pulse sequences in general require greater SAR. The summaries of the safety studies of DBS external electrodes and implants in MRI are listed in Table 2.…”
Section: Survey Of the Experimental Literature On The Safety Of Scalpmentioning
confidence: 99%
“…Finally, while this work addressed minimising tissue-heating by limiting the overall sequence SAR, the growing availability of multi-channel RF excitation technology could in the future offer alternative efficient methods of obtaining high quality images whilst controlling local RF power deposition to safe levels [56]. …”
Section: Discussionmentioning
confidence: 99%
“…In 2011 Eryaman et al demonstrated the possibility of modifying the electric field of an RF coil to generate regions of low E-field magnitude in the body without significantly altering the transmit sensitivity [14]. In 2012 it was shown that the low tangential electric field region of a linearly-polarized birdcage transmitter can be steered to coincide with a wire implant to reduce the SAR [16]. Recently, we demonstrated that at 1.5 T, this low-field region is thick enough to encompass a generic DBS lead with wire segments that were up to 60° out of plane, reducing the SAR at the implant tip by up to 500 fold below that of commercially available coils [18].…”
Section: Introductionmentioning
confidence: 99%